Antimicrobial peptide-modified AIE visual composite wound dressing for promoting rapid healing of infected wounds - Chen, Yi; Qian, Hongjin; Peng, Dandan; Jiang, Yan; Liu, Qiaolin; Tan, Yan; Feng, Longbao; Cheng, Biao; Li, Guilan (Frontiers in Bioengineering and Biotechnology, 2024)
Wound infection is a major problem faced during wound healing. Therefore, it is necessary to develop wound dressings with excellent antimicrobial properties. Here, a smart response system of PVA-TPE/HA-AMP/SF/ALG wound dressing was prepared by a combination of chemical cross-linking and freeze-drying methods. We grafted AMP onto HA to endow the wound dressing with bacterial resistance and slow release of AMP. At the same time, the system detects bacterial activity in real time for precise antimicrobial activity (through the use of PVA-TPE) and modulates inflammation to reduce bacterial infection (through the use of AMP). In addition, the PVA-TPE/HA-AMP/SF/ALG wound dressing has a good three-dimensional mesh structure, which promotes cell proliferation, enhances collagen deposition and angiogenesis, and thus effectively promotes rapid healing of infected wounds. Moreover, it can induce the expression of inflammatory factors such as VEGF, TNF-α, IFN-γ, IL-4 and TGF-β1 in infected wounds through the Wnt/CAMK/p-PKC signaling pathway, inhibit inflammatory responses, promote wound healing and reduce scar formation. Therefore, the PVA-TPE/HA-AMP/SF/ALG wound dressing smart response system shows great promise in infected wound healing.